THE USE OF ADVERTISEMENT BILLBOARD AS A MEDIA TO IMPROV THE STUDENTS TRANSLATION ABILITY AT SMK TRITECH INFORMATIKA MEDAN - Sina, Ibnu (BRIGHT VISION Journal of Language and Education, 2021)
This research was conducted to know and proving that The Advertisement Billboard can improve students’ translation mastery in learning English for a month researching. The subjects of this research were seventh grade students of SMK Tritech Informatika Medan in academic year of 2020/2021 that consisted of 20 students. This research was conducted by using classroom action research. This research was used pre-test and post-test data, interview sheet, observation sheet, diary notes, and documentation.The result of this research showed that there was an improvement of students’ vocabulary mastery. It could be seen by the mean of the pre-test was 56, the mean of the first cycle was 69.4, and the mean of second cycle was 83.6, these results mean showed that the mean in second cycle were better than the first cycle. The percentage of students who got point > 70 up also grew up. In the pre-test, there was nobody got point 70 up (0%). In the post-test I of cycle I, the result is good enough because the students who got point > 70 up there were 8 students (40%). It means that there was a good improvement about 23.92%. In the post-test II of cycle II, students who got point 70 up were 20 students (100%) and the improving was about 25.36%. For the total score of students’ improvement from pre-test to post-test of cycle II was 49.28%. In other words, the students’ vocabulary mastery has improved from the first meeting to the next one. For the hypothesis testing, it was used t-test formula from the computation, it could be seen that coefficient of t-table (2.09) with fact level α = 0.05 was 8.04 in the coefficient of t- observation (8.04) > t-table (2.09). Thus, alternative hypothesis (Ha) stating that The Advertisement Billboard as a media improved students’ translation mastery can be accepted and could make the class become alive, active and fun properly. Keyword: Advertisement Billboard, Students’ Translation Mastery